Sexual Identity On Novel Red, White & Royal Blue (2019):Abraham Maslow – Psychoanalysis Theory - Nurliana Mashuri, Aisyah; Nur Malasari, Yunita; Tri Santosa, Budi (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
LGBT is a legal thing to do in England society by free to loving someone regardless of gender. This article explain about how character Henry as a prince in the novel Red, White & Royal Blue who wants to proving his sexual identity in the society on the basis of some encouragement. In this research, we using the Psychoanalysis theory by A.H Maslow. The problem we raise is that there are still many England people who are still not confident and afraid to admit that they have same-sex attraction, especially public figure. And this research, our primer data is the novel Red, White & Royal Blue by Casey McQuiston. Data is analyzed by collecting word, sentences or paragraphs related to belongingness and love needs, esteem needs in Basic needs. And the data we collect, we explain about the character self actualization. The results of our research can be concluded that recieving encouragement from people closest and loved can be a factor for someone to be more brave in admitting something with more confidence. And every people is free to love and express themselves, and everyone has the right to determine their sexual identity.